E-learning and Physics Teaching Materials Based on Malay Ethnoscience on the East Coast - Irfandi, I.; Sudarma, T. F.; Festiyed, F.; Yohandri, Y.; Diliarosta, S.; Surahman, D.; Siregar, A. M. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
This study aims to create and develop a Learning Management System (LMS) and teaching materials for General Physics courses as well as to see the effectiveness of using LMS and Ethnoscience-Based Teaching Materials for East Coast Malay Culture, which are closely related to the tradition of weaving pandan leaves as household products and decorations, in Supporting a Valid, Practical and Effective Blended Learning System. This research is included in the research and development method involving 38 students majoring in Physics. The development steps were adapted from the model developed by Thiagarajan, with the implementation stages consisting of (1) define, (2) design, (3) development, and (4) Disseminate. The findings that were obtained in the implementation of this study were that a team of students validated the instrument as a whole to obtain an average gain from cycle I 0.58 (Moderate) and then increased in cycle II 0.64 (Medium) and Cycle III at 0.73 (High). Several conclusions can be drawn that teaching materials based on ethnoscience and LMS improve student learning outcomes and, have met the criteria set for use in lectures and can be uploaded to the learning system using blended learning.